Determination of an optimal pinch point temperature difference interval in ORC power plant using multi-objective approach. (20th April 2019) - Jankowski, Marcin; Borsukiewicz, Aleksandra; Szopik-Depczyńska, Katarzyna; Ioppolo, Giuseppe
Abstract : Organic Rankine Cycle (ORC) power plants are constantly developing systems and, apart from Stirling engine, are currently the only commercially available technology, which allows electricity generation using low and medium temperature waste thermal energy. A lot of effort has been devoted to improve analysis techniques, with the aim to find the most favorable parameters of ORC as well as the best working fluid for a certain type of energy source and configuration of the system. The aim of the paper is to present a method to determine an optimal pinch point temperature difference interval ( OPPTDI ) using multi-criteria approach with G(X) as multi-objective function and pinch point temperature difference as a decision variable. The analysis has been carried out for five selected organic fluids: R245fa, R1234yf, R1234ze, R227ea, and R152a. The optimization model has been solved using the linear weighted sum method. The applied technique specifies OPPTDI by assigning different values of weights w 1 and w 2 to the individual objective functions f 1 (economic index) and f 2 (environmental index), which are the components of the global function G . The proposed method should be perceived as an initial evaluation of the pinch point temperature difference interval, giving an insight for the designer what is the potentially optimal range of the considered quantity and moreover – the optimal values region of such parameter, if one of the objective functions is evaluated to be more significant than the other. Highlights: The geothermal Organic Rankine Cycle power plant is analyzed. The term of an optimal pinch point temperature difference interval is proposed. The objective functions f 1 (economic) and f 2 (environmental) are defined. The multi-criteria approach with G(X) as multi-objective function is applied. The optimal range of the pinch point temperature difference is indicated.